Study guides

☆☆

Q: How do you solve x plus 3 plus 6x plus 9 equals 0?

Write your answer...

Submit

Still have questions?

Related questions

x2 + 6x + 8 = 0 Solve for x.X = -2 or X = -4

A quadratic equation. If you wish to solve for x, you can do so as follows: -x2 + 6x + 7 = 0 x2 - 6x - 7 = 0 (x - 7)(x + 1) = 0 x ∈ {-1, 7}

6x +108=18y y=6x/18+108/18 y=x/3+6

(x-2)(x-4) x=2,4 ans

It is: 3x2+6x-11 = 0

6x + 5 = 0 (I'm assuming) 6x = -5x = -5/6

9x2+6x-8 = 0 (3x+4)(3x-2) = 0 Therefore: x = -4/3 or x = 2/3

6x - 6x = 0

From what i understand the equation is like this; (3 * 2 ) + 6x + 24 = 0 6 + 6x +24 = 0 6x = - 24 - 6 6x = - 30 x = - 5

7x + 2 = 6x + 2 if and only x = 0.

This quadratic equation has no solutions because the discriminant is less than zero.

umm i don't nko sorry call this number 1800 2536678 thnk u

y=6x² is already solved. the parabola will touch the x-axis at x=0.

x2+6x+9 = x+3 x2+6x-x+9-3 = 0 x2+5x+6 = 0 Solve by factoring or with the help of the quadratic equation formula: (x+3)(x+2) = 0 Therefore: x = -3 or x = -2

x+15+(-15)=6x+(15+(-15)=6x+(15-15)=6x+(0)=6x+0=6Add/subtract 0 from both sides,x=6

the answer is -3x = 0

6x+5=3x+5 5=9x+5 x=0

2x2+6x-8 = 72 2x2+6x-8-72 = 0 2x2+6x-80 = 0 (2x-10)(x+8) = 0

(3x - 7)(2x + 9) = 0 x = 7/3 or -9/2

many solutions

x^2 + 3x + 7 = 6x + 18 x^2 - 3x - 11 = 0

6x+2y-3 = 0 2y = -6x+3 y = -3x+3/2 in slope intercept form

x2 + 6x + 9 = 81 x2 + 6x = 72 x2 + 6x - 72 = 0 (x+12)(x-6) = 0 x= -12, 6 (two solutions)

3x(2x + 1)

2x2 - 6x + 4 = 0 2(x2 - 3x + 2) = 0 2(x - 1)(x - 2) = 0 x - 1 = 0 and x - 2 = 0 So, x = 1 and x = 2.